(3fRgI GdCQhGM hQhVI GdCaQGMs - (3eMeO Hf eMehO GdETQGbj GdTgQRhQj , TeS GdOjf,J (B687 (3g` s ((3HGjRjO Hf eMeO Hf ehSi GdLgQei GdOjdei s)
(3ChdgG (B:s
(3GdMeO ddg GdbOje GdCRdi GdOGFe s
(3GfXQ Qbe (B1082 (3JGQjN JMJ YfhGf (B"(3QhVI GdCaQGM hfRgI GdCQhGM(B"s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B87 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B320 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B136s
Keywords: (3GdJGQjNs